If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2) * 5 = 0 Reorder the terms: (-2 + x) * 5 = 0 Reorder the terms for easier multiplication: 5(-2 + x) = 0 (-2 * 5 + x * 5) = 0 (-10 + 5x) = 0 Solving -10 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 0 + 10 5x = 0 + 10 Combine like terms: 0 + 10 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 | | 3x-7=9+7x | | x+8=-2-x | | 15x^2+2xy-8y^2=0 | | 80x=-280 | | 100x=400 | | 2(x+2)=3(3x-4) | | 23x+10=28x+30 | | 21x+2=21x+11 | | 5-(2x+4)=3-(3x+2) | | x+24=24-y | | 12y^2-19y-21=0 | | x^4+4x=-c | | x^4+4x=c | | 4x+1+4c=5c-3x+6 | | 6y^2+23y+7=0 | | 3y^2-11y+10=0 | | 5x-8+3(2X-5)= | | 4y^2+9y+5=0 | | -2(x+3)=-2(x+5)-4 | | -2(x+3)=-2(x+2)-4 | | 2y^2+5y-12=0 | | 6y^2+5y-4=0 |